2015
DOI: 10.4047/jap.2015.7.3.233
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various veneering techniques on the marginal fit of zirconia copings

Abstract: PURPOSEThis study aimed to evaluate the fit of zirconia ceramics before and after veneering, using 3 different veneering processes (layering, press-over, and CAD-on techniques).MATERIALS AND METHODSThirty standardized zirconia CAD/CAM frameworks were constructed and divided into three groups of 10 each. The first group was veneered using the traditional layering technique. Press-over and CAD-on techniques were used to veneer second and third groups. The marginal gap of specimens was measured before and after v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 39 publications
2
53
0
2
Order By: Relevance
“…Some previous studies showed the variations in accuracy between the restorations with and without the porcelain build-up techniques and the significant effects of the veneering techniques on marginal accuracy 50,51) . This investigation, however, did not consider a veneer technique which was one of the limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies showed the variations in accuracy between the restorations with and without the porcelain build-up techniques and the significant effects of the veneering techniques on marginal accuracy 50,51) . This investigation, however, did not consider a veneer technique which was one of the limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Veneering may have a significant influence on the marginal fit of zirconia restorations. [43][44][45] However, as monolithic zirconia crowns are not veneered but characterized only with staining through glazing, 46 how the marginal fit of the monolithic zirconia crowns is affected by the fabrication stages is important. Cementation may also affect the marginal fit of ceramic crowns.…”
mentioning
confidence: 99%
“…Actually high quality, all-ceramic restorations are not easily distinguished from adjacent natural teeth. 13 Among the many ceramic systems that have been developed, Yttria-stabilized polycrystalline tetragonal zirconia has become a common form of dental restoration; mostly because of having good characteristics including esthetics, excellent biocompatibility, low plaque accumulation, and high strength 14 . In addition to esthetics, marginal fit and fracture strength are essential criteria for clinical success.…”
Section: Discussion:-mentioning
confidence: 99%